Dietary Nitrate Supplementation Alters Protein and Lipid Metabolism in Zebrafish (Danio rerio) Livers. (7th June 2021) - Keller, Rosa; Beaver, Laura; Reardon, Patrick; Stevens, Jan; Hord, Norman
Abstract: Objectives: Dietary nitrate supplementation shows protective effects against cardio-metabolic disease, decreases pulmonary oxygen uptake, and improves exercise performance in animal models and humans. However, the biological effect of nitrate on energy metabolism in the liver is not well understood. The objective of this study was to elucidate changes in liver metabolism associated with nitrate treatment and exercise. Methods: Fish were exposed to sodium nitrate (606.9 mg/L), or control water, for 21 days and analyzed at intervals during a strenuous exercise test. We utilized untargeted liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis to determine the effect of nitrate treatment and exercise on the liver metabolome. We measured gene expression of 31 genes linked to energy metabolism and redox signaling. Results: In the absence of exercise, nitrate treatment upregulated expression of genes central to nutrient sensing ( pgc1a and sirt3 ), protein synthesis ( mtor ) and purine metabolism ( pnp5a and ampd1 ) and downregulated expression of genes involved in mitochondrial fat oxidation ( acaca, cpt2 and hadh ). Upregulation of these genes was associated with an increased abundance of metabolites involved in endogenous nitric oxide metabolism, dopamine biosynthesis, branched chain amino acid metabolism, and lipid metabolism in nitrate-treated livers at rest, compared to rested controls. As expected, the availability of these metabolites was diminished in nitrate-treated livers relative to rested controls. We found no significant change in gene of metabolites directly linked to glycolysis. Conclusions: The main novel finding of this study was that sub-chronic nitrate treatment altered dopamine biosynthesis, protein synthesis and lipid metabolism in zebrafish liver without exercise. This is significant because dietary nitrate is emerging as an interesting therapeutic modality for metabolic syndrome and non-alcoholic fatty liver disease by preventing lipid accumulation in the liver. Funding Sources: Celia Strickland and G. Kenneth Austin III Endowment and National Institutes of Health.